Extending the Mind Conservatively - Boghitoi, Bogdan (Filozofia Nauki, 2015)
The paper provides an alternative argument for the extended mind thesis. It shows that parity based approaches are ultimately ineffective, because they are too liberal with what we are to count as cognitive and thus unacceptably revisionist about the way science in general divides nature. The present analysis points to the way science deals with nonstandard biological mechanisms as a possible basis for the extended mind thesis. This is not only more consistent with solidly established bodies of knowledge but also makes the extended mind an offshoot of the usual way we build our scientific theories. Furthermore, certain technological achievements, such as sensory substitution systems, show that the extended mind is an effective reality, not only a conceptual possibility, and sometimes it is the only option we have in order to construct explanations or experiments.